2011
DOI: 10.1016/j.mce.2010.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin up-regulation is associated with the skeletal muscle response to hypoxic stimuli

Abstract: Myostatin up-regulation is associated with the skeletal muscle response to hypoxic stimuli, Molecular and Cellular Endocrinology (2010), doi:10.1016/j.mce.2010 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
55
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 66 publications
9
55
1
Order By: Relevance
“…Such results could have medical relevance for patients suffering from chronic obstructive pulmonary diseases (COPD). Skeletal muscle atrophy and weakness in these patients are partly attributed to hypoxia (52) and are associated with an activation of REDD1 (16) and myostatin (20). Our preliminary data support the notion that anabolic signals related to functional load are able to counteract the increased expression of these two repressors of muscle mass during hypoxia exposure.…”
Section: Perspectives and Significancesupporting
confidence: 78%
See 2 more Smart Citations
“…Such results could have medical relevance for patients suffering from chronic obstructive pulmonary diseases (COPD). Skeletal muscle atrophy and weakness in these patients are partly attributed to hypoxia (52) and are associated with an activation of REDD1 (16) and myostatin (20). Our preliminary data support the notion that anabolic signals related to functional load are able to counteract the increased expression of these two repressors of muscle mass during hypoxia exposure.…”
Section: Perspectives and Significancesupporting
confidence: 78%
“…Here, we showed that myostatin, another negative regulator of muscle growth (3), was early activated by hypoxia in Ct muscles, but this upregulation was minimized by functional overload. This finding confirms the role played by hypoxia on myostatin expression (20), but it rejects its involvement in explaining the inhibitory effect of hypoxia on muscle hypertrophy.…”
Section: R651supporting
confidence: 67%
See 1 more Smart Citation
“…Indeed, chronic restriction of blood flow resulted in a drop in the myostatin content in rats (49). However, myostatin upregulation was associated with the skeletal muscle response to hypoxia-mimicking agents in vitro (50).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that chronic exposure to hypoxia adversely affects protein kinase B/mTOR signalling [123], up-regulates myostatin expression [124], and subsequently leads to atrophy in skeletal muscle [125].…”
Section: Intramuscular Signalling Pathwaysmentioning
confidence: 99%